EKSISTENSI TARI DROP DARUET DARI ACEH PIDIE DAN UPAYA PELESTARIAN DI ERA MODERNISASI - Sabri Gusmail; Khairul Anwar (TANDIK : Jurnal Seni dan Pendidikan Seni, 2021)
Drop Daruet dance as a legacy of regional cultural events still exists today. The purpose of this study was to determine the existence of the Drop Daruet dance in the modernization era, to determine the efforts to preserve the Drop Daruet dance. The research location is in the Cut Nyak Dhien Meligoe studio, the Governor of Aceh. This type of research is a qualitative research with a case study method. The main data sources were obtained from interviews with informants, while other data sources were obtained from observation and documentation study. Data collection techniques used observation and in-depth interviews with informants (administrators, coaches, dancers, musicians and the community). The analysis technique uses an interactive data analysis model, namely data collection, data reduction, data presentation, and drawing conclusions. The results showed that the Drop Daruet dance is a traditional folk dance that is not widely known by the public and there is little information about the existence of this dance. Drop Daruet dance is defined as an art form that has roots and is felt as its own by the Cut Nyak Dhien Meuligoe studio, the Governor of Aceh or its environment. The efforts made in the management of the dance are only based on the taste of the supporting community which is carried out from time to time and is passed on in a regenerative manner. In its development, this dance becomes an entertaining performance art, but it still keeps messages from the form of dance movements that can be easily understood by the public